Padiberas Nasional Berhad (BERNAS): a symbol of corporate social responsibility / Siti Sarah Azidin and Nor Diyana Ros - Azidin, Siti Sarah; Rosli, Nor Diyana (2010)
This study examines on the importance of implementing corporate social responsibility in an organization. Corporate social responsibility refers to an obligation of an organization's management towards the welfare and interests of the society, which provides the environment and resources to survive and grow, and which is affected by the organization's actions and policies. In other words, corporate social responsibility is a concept whereby companies decide voluntarily to contribute to create a better society.